Preprocessing Factors Affected Free Fatty Acid Content in Crude Palm Oil Quality - Edyson Edyson; Fitrah Murgianto; Adhy Ardiyanto; Erika Juli Astuti; Melina Putri Ahmad (Institut Pertanian Bogor, 2022)
The quality of CPO (Crude Palm Oil) is determined by the Free Fatty Acid (FFA) with the standard value below 5%. High FFA in CPO will cause further difficulties due to low refining rate and quality like rancidness and odor. The objective of this research was to determine the factors that affect the FFA content in CPO. This research was conducted from January until April 2021. Fruit samples were collected from BKLE and PNRE East Kotawaringin and analyzed to Analytical Laboratory PT BGA. The FFA value was determined using the titration method according to Indonesian National Standard (SNI). Based on this research, several factors such as rat and moth attacks, fruit maturity, fruit handling, and delayed delivery to the palm oil mill affected the FFA value. These factors caused an increase in the FFA value up to 41.10%‒204% compared to the average FFA value is only 0.77%‒1.29%. Therefore, minimizing the pre‐processing problem will reduce the potential of FFA value increment so that good quality CPO can be obtained. Keywords: fruit handling, fruit maturity, pest attack, titration method